Unveiling the Factors behind the Lack of Human Anatomy Knowledge in Traditional Chinese Medicine - Zhang, Luwen (Journal of Biology and Life Science, 2024)
Traditional Chinese Medicine (TCM) is a holistic approach to healthcare that has been practiced for thousands of years. TCM offers effective treatments for a wide range of health conditions. However, in comparison to modern medicine, TCM places less emphasis on human anatomy in its diagnostic and treatment practices and has not developed a comprehensive system of human anatomy. By delving into the history, traditions, religion, and practice of TCM, the factors that have limited the development of human anatomy in TCM are identified. Firstly, reverence for tradition and religion may have suppressed motivation for advancement in this area. Secondly, the subjective nature of diagnosis and evaluating treatment outcomes in TCM reduces the necessity of studying human anatomy. Thirdly, the traditional education system in China had hindered the integration of human anatomy into TCM. Finally, cultural perspectives that prioritize the body as an integrated whole have also influenced the development of TCM. The findings of this study offer valuable insights into the unique perspectives and values associated with TCM. Bridging the gap between ancient wisdom and modern science will allow TCM to evolve while retaining its core principles. The integration of human anatomy into TCM will rejuvenate the whole research field by providing new insights into the mechanisms of TCM and maximize its potential in treating a wider range of diseases. TCM has made tremendous contributions to human health in the past and will continue to do so in the present and future.